Pengaruh Latihan Kekuatan Otot Lengan Hasil Tembakan Freethrow Terhadap Siswa Ekstrakurikuler Basket SMA Laboratorium UM - Supriyadi Supriyadi; Dinta Sugiarto; Nila Dwi Rarasanti (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this study was to determine the effect of arm muscle strength on the results of free throws for extracurricular basketball students at SMA Laboratory, State University of Malang. The method used in this research is to use experimental research which allows processing of specimens (subjects), conditioning and measurement to further optimize the results obtained from this study. The results of this study tested the effect of arm strength training using the push-up technique on the results of free throw shots of basketball extracurricular students at Laboratory High School, State University of Malang by using a paired sample t test. The pretest and posttest values show a tcount of 6.376 and a ttable value of 2.093, so it can be concluded that 6.376 (tcount) > 2.093 (ttable). Based on the results of the study, it can be concluded that this study had a significant effect during arm strength training using the push-up technique on the free-throw results of basketball extracurricular students at the SMA Laboratory, State University of Malang.